Investigating the impact of long-term bristlegrass coverage on rhizosphere microbiota, soil metabolites, and carbon–nitrogen dynamics for pear agronomic traits in orchards - Shi, Chunhui; Wang, Xiaoqing; Jiang, Shuang; Xu, Jianfeng; Luo, Jun (Frontiers in Microbiology, 2024)
Grass coverage (GC) under no-tillage systems significantly influences underground carbon (C) and nitrogen (N) sequestration, primarily through promoting mineral nutrient utilization by rhizospheric microorganisms. However, the comprehensive impact of GC on microbial communities and plant responses using soil metabolomics remains inadequately recognized. In this study, we investigated two rhizosphere types established since 2002:bristlegrass coverage (SC) and clean cultivation (CC) to assess their effects on soil parameters, enzyme activities, and key pear agronomic traits, including yield (single fruit weight (SFW) and qualities (soluble solids content (SSC), and total soluble sugar (TSS)).We combined microbiological analysis (16S rRNA sequencing) and non-targeted metabolomics (UPLC-MS/MS and GC-MS) to explore how microbial communities influence fruit agronomic traits and soil nutrient dynamics in pear orchards under SC conditions. Our findings indicate that SC significantly enhances soil organic carbon (SOC), soil organic nitrogen (SON), C:N ratio and available nitrogen (AN). Moreover, SC leads to pronounced increases in soil enzyme activities involved in the C cycle and storage, including soil sucrase, β-glucosidase, polyphenol oxidase and cellulase. Microbiome analysis revealed substantial differences in microbial community composition and diversity indices between SC and CC rhizosphere soils within the 0-40 cm depth. Significant alterations in metabolite profiles across both the 0-20 cm and 20-40 cm layers under SC conditions. The identified metabolites primarily involve sugar and amino acid-related metabolic pathways, reflecting perturbations in C and N metabolism consistent with shifts in bacterial community structure.Several plant growth-promoting rhizobacteria (PGPRs) taxa (e.g., Haliangium, Bacteroides, mle1-7, Subgroup22, Ellin6067, MND1, Flavobacterium and Cellvibrio) were enriched under SC, associated with metabolites such as sucrose, N-acetyl-D-glucosamine, N-acetyl-L-glutamic acid, rhamnose, UDP-GlcNAc, and D-maltose. These findings suggest their roles in promoting C and N sequestration processes through sucrose synthesis and glycolytic pathways in the soil, which was significantly correlated with the formation of agronomic traits such as yield, SFW, SSC and TSS, SC treatments significantly increased yields by 35.40-62.72% and sucrose content in TSS by 2.43-3.96 times compared to CC treatments. In conclusion, this study provides valuable insights into the effects of SC on soil microbial communities and plant physiology, enhancing our understanding of their implications for sustainable orchard management.